Poverty implications of agricultural land degradation in Ghana: An economy-wide, multimarket model assessment - Diao, Xinshen; Sarpong, Daniel Bruce (Wiley, 2011)
Abstract:  An economy‐wide, multimarket model is applied for Ghana and is used to assess the aggregate economic cost of agricultural soil erosion. To fill a gap in the literature regarding economic cost analysis of soil erosion, this paper also analyzes the poverty implications of land degradation. The model predicts that land degradation reduces agricultural income in Ghana by a total of US$4.2 billion over the period 2006–2015 and the national poverty rate will increase in 2015 by 5.4 percentage points. Moreover, soil loss causes a slowing of poverty reduction over time in the three northern regions, which currently have the highest poverty rates in the country. Sustainable land management (SLM) is the key to reducing agricultural soil loss. The present findings indicate that through the adoption of conventional SLM practices, the declining trend in land productivity can be reversed, and that use of a combination of conventional and modern SLM practices would generate an aggregate economic benefit of US$6.4 billion over the period 2006–2015. SLM practices would therefore substantially reduce poverty in Ghana, particularly in the three northern regions.